2020
DOI: 10.28991/cej-2020-03091500
|View full text |Cite
|
Sign up to set email alerts
|

Healing of Generated Cracks in Cement Mortar Using MICP

Abstract: This research is carried out to investigate pre-existing repair cracks in cement mortar using the microbiologically induced calcium carbonate precipitation (MICP) technology. In the study, 20-cylinder mortar samples (45 mm in diameter and 40 mm in length) were split to have cracked width of various sizes. Out of twenty cracked samples, sixteen samples of average crack width ranging from 0.12 to 1.3 mm were repaired using the MICP method, while four cracked samples, with an average crack width ranging from 0.16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…XRD analysis showed that CaCO 3 in calcite form was present in both ancient bricks and MICP filler. On one hand, this result validated that S. pasteurii can successfully utilize chemical components to produce CaCO 3 in the brick cracks; this suggests that S. pasteurii has a similar function to that of Bacillus subtilis species as presented in former MICP-related studies [19,30]. On the other hand, the generated CaCO 3 by MICP appears in calcite form, which is the same form as that of the ancient bricks in this study.…”
Section: Materials Chemistry and Mineralogy After Micp Treatmentsupporting
confidence: 83%
See 1 more Smart Citation
“…XRD analysis showed that CaCO 3 in calcite form was present in both ancient bricks and MICP filler. On one hand, this result validated that S. pasteurii can successfully utilize chemical components to produce CaCO 3 in the brick cracks; this suggests that S. pasteurii has a similar function to that of Bacillus subtilis species as presented in former MICP-related studies [19,30]. On the other hand, the generated CaCO 3 by MICP appears in calcite form, which is the same form as that of the ancient bricks in this study.…”
Section: Materials Chemistry and Mineralogy After Micp Treatmentsupporting
confidence: 83%
“…The remediation of the surface cracks of the ancient bricks involved the configuration and curing of certain sodic particles; the process of bio-calcification during MICP could form CaCO 3 crystals, which could, in turn, be used to fill and bind the generated gaps of the deteriorated masonry [ 18 , 19 ]. In our study, we show that MICP can efficiently remediate both the natural and simulated cracks in the ancient bricks.…”
Section: Discussionmentioning
confidence: 99%
“…Portland cement is the material most widely used in the construction industry worldwide and it is estimated that its production releases approximately 7.4% of global anthropogenic emissions of carbon dioxide [1]. The cement industry follows several levers to reduce the unavoidable environmental effects of producing Portland cement, but probably, among all of them, the increase of the period of service-life of the cement-based materials is most important, for instance, by crack reduction [2]. Kulkarni et al (2020) used the technology named "microbiologically induced calcium carbonate precipitation (MICP)" to repair cracks and they found a reduction in permeability in the range from 65 to 85% for cracks ranging from 0.12 to 1.3 mm [2].…”
Section: Introductionmentioning
confidence: 99%
“…The cement industry follows several levers to reduce the unavoidable environmental effects of producing Portland cement, but probably, among all of them, the increase of the period of service-life of the cement-based materials is most important, for instance, by crack reduction [2]. Kulkarni et al (2020) used the technology named "microbiologically induced calcium carbonate precipitation (MICP)" to repair cracks and they found a reduction in permeability in the range from 65 to 85% for cracks ranging from 0.12 to 1.3 mm [2]. The second one could be the production of blended cements.…”
Section: Introductionmentioning
confidence: 99%
“…The desorption of absorbed water from SAP also conserves high internal relative humidity of mortar and thereby mitigate shrinkage of mortar [11,21,22]. Various methods have been investigated to produce self-healing concrete incorporating mineral admixtures as well as bacteria [23,24]. SAP also can be applied to reduce the potential cracking [25,26] as well as to induce self-sealing [27][28][29] of cementitious materials due to the characteristics of SAP, i.e.…”
mentioning
confidence: 99%